Polyherbal formulation PL02 alleviates pain, inflammation, and subchondral bone deterioration in an osteoarthritis rodent model - Upadhyay, Prabhat; Kalra, Diya; Nilakhe, Aishwarya Shrikant; Aggrawal, Vijay; Gupta, Sarika (Frontiers in Nutrition, 2023)
Osteoarthritis (OA) is a debilitating disease with significant personal and socioeconomic burdens worldwide. To address this, we developed a multitargeted formulation called PL02, which includes standardized extracts of Rosa canina L, Hippophae rhamnoides, and collagen peptide.We tested the pharmacological efficacy of PL02 in a rodent model of OA induced by Monosodium iodoacetate (MIA). Our results demonstrate that oral administration of PL02 has antioxidant effects by down-regulating NOS, reduces pain-related behavior, and mitigates inflammation by inhibiting IL-1b and TNF-α production, as well as downregulating CGRP1 and COX-II. PL02 also exhibits anti-catabolic and chondroprotective activity by significantly downregulating MMP13 and upregulating BCL2. Additionally, PL02 demonstrates chondrogenic activity by significantly upregulating SOX-9 (a master regulator of chondrogenesis), Coll-I, and aggrecan, which are major components of articular cartilage. Furthermore, PL02 prevents microarchitectural deterioration of subchondral bone. Overall, PL02 is an orally active, multitargeted therapy that not only alleviates pain and inflammation but also effectively halts cartilage and subchondral bone deterioration. It represents a safe and promising candidate for the treatment and management of OA.